OP0082 Expression of Fractalkine in Sjögren's Syndrome Patients: Cellular and Molecular Characterization of CX3CL1 and CX3CR1 in Sera and Salivary Glands. (23rd January 2014) - Astorri, E.; Scrivo, R.; Bombardieri, M.; Picarelli, G.; Pecorella, I.; Porzia, A.; Valesini, G.; Priori, R.
Abstract : Background: Primary Sjögren's syndrome (SS) is an autoimmune disease characterized by chronic lymphocytic inflammation and destruction of acinar tissue within the salivary glands (1 ). Fractalkine (CX3CL1, FKN) is the sole member of the CX3C chemokine family and acts as an adhesion and chemotactic molecule. FKN has been associated with the pathogenesis of rheumatoid arthritis (RA) and studies in the salivary glands of non-obese diabetic mice (NOD) view it as a potential new autoantigen in SS(2, 3 ). Furthermore, it is possible that IL-23 may be upregulated in cells exposed to a higher than physiological concentration of FKN, affecting Th17 polarization and the development and/or onset of SS. Objectives: To what extent CX3CL1 and its receptor CX3CR1 expression might be altered in salivary glands obtained from patients with SS remained to be investigated. Methods: Twenty-one patients with primary SS, 11 patients with Sicca Syndrome (SICCA), 20 RA patients and 10 blood donors were recruited for this study. In order to establish whether FKN might represent a marker and an antigen for SS we performed a detailed and comprehensive assessment of the presence of FKN protein and anti-FKN antibodies in sera by ELISA and WB respectively. From a molecular point of view we studied by TaqMan RT-PCR CX3CL1 and CX3CR1 mRNA expression in salivary glands of patients and we correlated it to IL23 and IL17 mRNA levels. All data were compared with patients' clinical information. Histological evaluation was performed on sequential sections. Results: Increased serum levels of CX3CL1 protein were observed in SS patients compared to controls (p<0.0001), in RA patients compared to controls (p<0.0001) but no difference was found between SICCA and controls (p=0.22). The mRNA levels of the chemokine and its receptor were upregulated in SS salivary glands, as compared to SICCA salivary glands. Autoantibodies were detected in 23.8% of SS patients. Finally we identified histologically the cells expressing CX3CL1 and CX3CR1 in salivary glands of SS patients and we localized the molecule within tertiary lymphoid structures. Conclusions: We believe that our findings allow considering future studies on FKN protein and autoantibody as new tools in the evaluation and diagnosis of SS. References: Bombardieri M, Barone F, Humby F, Kelly S, McGurk M, Morgan P, et al. Activation-induced cytidine deaminase expression in follicular dendritic cell networks and interfollicular large B cells supports functionality of ectopic lymphoid neogenesis in autoimmune sialoadenitis and MALT lymphoma in Sjogren's syndrome. J Immunol. 2007 Oct 1;179(7):4929-38. Imai T, Hieshima K, Haskell C, Baba M, Nagira M, Nishimura M, et al. Identification and molecular characterization of fractalkine receptor CX3CR1, which mediates both leukocyte migration and adhesion. Cell. 1997 Nov 14;91(4):521-30. Murphy G, Caplice N, Molloy M. Fractalkine in rheumatoid arthritis: a review to date. Rheumatology (Oxford). 2008 Oct;47(10):1446-51. Disclosure of Interest: None Declared